CONSTITUTIONAL AND LEGAL ENSURING OF THE PROTECTION OF COMPETITION IN BUSINESS ACTIVITY IN UKRAINE: PROBLEMS OF THEORY AND PRACTICE - Shatilo, Volodymyr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to characterize the problems of the theory and practice of constitutional and legal protection of competition in business activity in Ukraine as a single system of constitutional norms and offer ways to solve them. Research methods: dialectical, systemic, analysis and synthesis, generalization. Results: theoretical and practical problems of constitutional and legal provision of competition in business activity were determined and ways of their solution were proposed. Discussion: a systemic problem of business activity and competition protection is the excessive intervention of state authorities in the activities of economic entities, the external manifestations of which are deficiencies in the regulatory and legal regulation of business activity and competition protection and law enforcement deficiencies. There are the shortcomings of the legal regulation of business activity and protection of competition: 1) the uncertainty of the priority of legislative acts regarding the regulation of business activity and competition; 2) complexity and volume of the regulatory framework; 3) instability and internal inconsistency of legislative acts; 3) lack of mechanisms for their implementation in the laws. The shortcomings of law enforcement include: 1) unsatisfactory executive discipline, including by the subjects of entrepreneurial activity themselves; 2) inconsistent practice of law enforcement due to insufficient legal certainty of the legislation; 3) recklessness policy in the field of competitive environment formation. These problems can be eliminated by adopting a single codified act, which would regulate all aspects of state protection of competition, and the concept of competition protection, which would be based on the provisions of the EU acquis and Chapter 10 of the Association Agreement and would become the basis for the development of a state strategy for the protection of competition.